Wspomnienie o matce Joannie Marii Korytko (1887-1958) Przyczynek do historii poznańskich karmelitanek bosych - Neumann, Piotr Franciszek (Ecclesia. Studia z Dziejów Wielkopolski, 2018)
The remembrance of Mother Joanna Maria Korytko (1887-1958), a Discalced Carmelite nun was written by one of her fellow sisters at the Carmelite convent in Poznań, Sister Maria Józefa Szweda. Until recently it was only in manuscript version. The text represents a literary trend known as convent writings which has a long and rich tradition among Discalced Carmelites. Mother Joanna Maria of the Most Sacred Heart of Jesus (Teresa Korytko) came from a landed gentry family in Podolia. After obtaining an education at the Sacré-Coeur boarding school in Prague and Zbylitowska Góra as well as at the school run by Jadwigi Zamoyska in Kuźnice, in 1907 she joined the convent of Discalced Carmelites in Kraków at Łobzowska Street. In the years 1920-1940 she lived at the newly founded convent in Poznań at Niegolewskich Street. She spent the period of German occupation in Kraków and after the end of the Second World War returned to Poznań where she served as mother superior of the community of nuns. Faced by the loss of the previous residence she organized a convent at a new location at St. Adalbert Street. She fulfilled the responsibilities of mother superior for twelve years distinguishing herself by her deep spiritual life and  aithfulness to the charism of St. Teresa of Jesus.